Adsorption of the prototypical organic corrosion inhibitor benzotriazole on the Cu(100) surface. (October 2022) - Turano, Marco; Walker, Marc; Grillo, Federico; Gattinoni, Chiara; Hunt, Gregory; Kirkman, Paul; Richardson, Neville V.; Baddeley, Christopher J.; Costantini, Giovanni
Abstract: The interaction of benzotriazole (BTAH) with Cu(100) has been studied as a function of BTAH exposure in a joint experimental and theoretical effort. Scanning tunnelling microscopy (STM), X-ray photoelectron spectroscopy (XPS), high resolution electron energy loss spectroscopy (HREELS) and density functional theory (DFT) calculations have been combined to elucidate the structural and chemical characteristics of this system. BTAH is found to deprotonate upon adsorption on the copper surface and to adopt an orientation that depends on the molecular coverage. Benzotriazolate (BTA) species initially lie with their planes parallel to the substrate but, at a higher molecular coverage, a transition occurs to an upright adsorption geometry. Upon increasing the BTAH exposure, different phases of vertically aligned BTAs are observed with increasing molecular densities until a final, self-limiting monolayer is developed. Both theory and experiment agree in identifying CuBTA and Cu(BTA)2 metal-organic complexes as the fundamental building blocks of this monolayer. This work shows several similarities with the results of previous studies on the interaction of benzotriazole with other low Miller index copper surfaces, thereby ideally completing and concluding them. The overall emerging picture constitutes an important starting point for understanding the mechanism for protection of copper from corrosion. Highlights: Benzotriazole molecules deprotonate upon room temperature deposition on Cu(100). The molecules change from a flat to an upright adsorption configuration with increasing coverage. They form a self-limiting densely packed monolayer. The molecular layers are composed of strongly bound Cu(BTA) and Cu(BTA)2 metal-organic complexes.